HUBUNGAN GLYCATED ALBUMIN DENGAN ANGKA BANDING KOLESTEROL LDL/LDH DI DIABETES MELITUS TIPE 2 (Association of Glycated Albumin with LDL/HDL Cholesterol Ratio in Type 2 Diabetics) - Tiwik Eriskawati; Tahono Tahono; M.I. Diah. P (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Diabetes causes about 5% of all deaths globally each year. Glycated hemoglobin has been routinely used as a biomarker for long-termglycemic control. Glycated albumin is an intermediate glycemic marker, a potent atherogenic protein, which plays a role in developingatherosclerosis. LDL/HDL cholesterol ratio can be used to assess the risk of cardiovascular disease caused by impaired lipid metabolismin type 2 diabetic patients. The aim of this study was to know the association between GA and HbA1c with LDL/HDL cholesterol ratioin type 2 diabetic patients. The study was carried out by a cross sectional design. Eighty four type 2 diabetic patients admitted to theInternal Medicine Outpatient Clinic of the Dr. Moewardi Hospital who met the study inclusion criteria were studied. Linear Regressionand Chi Square tests were used to analyze the data, p value of <0.05 was considered statistically significant, with the confidenceinterval of 95%. In this study, significant associations between GA and HbA1c with LDL/HDL cholesterol ratio (R=0629 and R=0.501,p=0.001) were found. Type 2 diabetic patients with GA ≥17% obtaining LDL/HDL cholesterol ratio >1.85 was 10.33 greater thanthose of with GA <17% (RP=10.33; CI 95%; 1.01–109.49; p=0.018). While type 2 diabetic patients with HbA1c ≥7% obtaining anLDL/HDL cholesterol ratio >1.85 was 12.76 greater than those with HbA1c <7%, but was statistically not significant (RP=12.76; CI95%; 0.66–245; p=0.017). Based on this study it can be concluded that GA can be used to predict LDL/HDL cholesterol ratio. Thus,GA is superior to HbA1c in predicting LDL/HDL cholesterol ratio.